Dualisme pasar dan ketimpangan Pembangunan : tinjauan ekonomi sturuktural - Mahmadah, Fina; Nuroh, Lailin (CV. ITTC INDONESIA, 2026)
This study uses a structural economics perspective to examine the phenomenon of market dualism and its relationship to development inequality. Unequal development is caused by economic dualism, where modern and traditional sectors coexist, leading to differences in productivity, wages, and access to resources. This study investigates the structural mechanisms that reinforce market dualism and impact regional disparities and income distribution using a qualitative approach through literature review and secondary data analysis. The results indicate that some of the main barriers to structural transformation are structural rigidity, labor market division, and limited mobility of production factors. Market dualism causes vertical and horizontal differences among income groups. To address dualism and promote more equitable development, this study suggests an integrative structural transformation policy that includes infrastructure investment, human resource development, institutional reform, and inclusive industrialization.